Challenges during unwanted pregnancy among Malays teenage mother / Afiqah Ismail and Tuan Nor Ashikin Tuan Him - Ismail, Afiqah; Tuan Him, Tuan Nor Ashikin (2019)
Background: The phenomenon of ex-nuptial pregnancy among teenagers in Malaysia is a public concern. It associates with various negative consequences to the young mothers, their baby, family and the public as a whole. Despite the substantial effects, little is known about this phenomenon from the perspective of the young women themselves. Objective: This study aimed to explore the challenges of lived experiences of having unintended teenage pregnancy and to understand the strategies addressing this phenomenon from the perspective of the previously or currently unwed pregnant girls or young women. Methods: A qualitative study was conducted among 10 women who have experienced being unwed mothers when they were between 10 to 19 years old. Participants were recruited during their stay at two shelters in Selangor. All participants gave informed consent. In-depth face-to-face interviews were conducted, audiotaped and transcribed. All quotes were encoded using Qualitative Data Analysis (QDA) Miner program. Data were analyzed using interpretative phenomenological analysis (IPA). Results: Four themes emerged from the analyses; i) Trajectory of sexual activity, ii) struggles of motherhood to unwed teenage mothers, iii) The formula of resilience of teenage mothers, and iv) life after the misery. The girls and young women described how indirect relationships (such as communication via telephone and the internet) would increase the desire for sexual activities. Having broken family, poor religious practice, peer pressure and lack of knowledge on sexuality and reproductive health were described as the main contributing factors. They shared the difficulties to control the obsession or addiction to having sexual activities. They were overwhelmed with ambivalent feelings of wanting to terminate the pregnancy, abandon the newborn or to endure the journey of motherhood together with their ex-nuptial baby. With good support, the girls and young women managed to be good mothers for their baby. Conclusion: Perspectives of the girls and young women on addressing unwed teenage pregnancy are vital. Good support system and comprehensive strategies could assist them to cope with the challenges, continue their pregnancy and have a better life after the misery.